RANCANG BANGUN SISTEM PENILAIAN PRAKTEK KERJA LAPANGAN MENGGUNAKAN MACRO VB DAN CLOUD STUDI KASUS : POLITEKNIK STMI JAKARTA - Denny Rianditha Arief Permana (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
AbstractVocational education or also called vocational education is education that is special (specialized) which includes all types of work. Vocational education is not limited to education that only focuses on skills guidance. But actually vocational education is also concerned with the mentality, values, and attitudes of the community (students).Â Students who have finished field practice will be given a score in the form of a piece of paper and the score will be given to the field practice supervisor at the STMI Polytechnic. This activity creates risks because students can commit fraud, students can be careless and so on, which makes the value can be changed, damaged and lost does not reach the supervisor at the STMI Polytechnic. From the problems above, the most appropriate thing to do is to connect directly between the field supervisor and the supervisor at the STMI Polytechnic with an assessment system. The purpose of making this system is to reduce cheating and careless acts of students who make replaced or damaged grades. In making this system the author uses VB macro tools and Cloud itself. The system development method used is SDLC. The system development method is the SDLC (System Development Life Cycle) method or often referred to as the waterfall approach. This method allows for departmentalization and control. the process of developing the model phase one by one, so as to minimize errors that might occur.Â Keywords: PKL Value, Macro VB,S DLC.